CHARACTER EDUCATIONAL VALUE OF STEPHEN HAWKING IN THE THEORY OF EVERYTHING MOVIE DIRECTED BY JAMES MARSH - Mardewi, Tati; Indriyani, Furi (Universitas Nusantara PGRI Kediri, 2020)
The purpose of the research is to analyze educational values from the Theory of Everything movie directed by James Marsh. It discusses about educational values that are shown in and depicted by Stephen Hawking. Educational values are never give up, self-confidence, love, friendly and polite, optimism, help each other, responsible and hard working. Theory of Everything is a perfect movie for analyzing educational values, as it tells about the life of Stephen hawking who tries keeping himself in fire even though there are so many inside and outside obstacles. Some scenes in this movie show in Educational values. After doing some processes of observation from many opinions of experts, journals, books, social media, Education value is education in the concerned with the development of the total personality of the individual intellectual, social, emotional, aesthetic, moral and spiritual. It involves developing sensitivity to the good, the right and the ability to choose the right values in accordance with the thought and action. So educational values that are shown by Stephen hawking can make us know how to be succeeded to reach our ambition.